Zn-MOF (at) Ru / MIP electrochemical luminescence sensor, preparation method and application thereof, and method for visually detecting captopril drug by using sensor
By preparing Zn-MOF@Ru/MIP electrochemiluminescence sensor and combining with smartphone electrochemiluminescence microscope, the problem of high cost of electrochemiluminescence microscope devices in the prior art and failure to realize drug imaging detection is solved, and the drug cardot is realized Pril's visual detection and efficient imaging are suitable for the field of drug research.
Patent Information
- Application Number
- CN202411284427.9
- Authority / Receiving Office
- CN · China
- Patent Type
- Applications(China)
- Current Assignee / Owner
- Filing Date
- 2024-09-13
- Publication Date
- 2024-12-13
AI Technical Summary
The existing electrochemiluminescence microscope devices are costly and difficult to assemble, and have failed to achieve quantitative detection of drug imaging. There are no related reports on Zn-MOF@Ru based on captopril as a template for drug imaging.
Prepare Zn-MOF@Ru/MIP electrochemiluminescence sensor, and drip the Zn-MOF@Ru aqueous solution and film-forming agent on the surface of the electrode, and then drip the molecular imprinted polymer containing captopril as the template to construct A sensor with excellent electrochemiluminescence performance and continuous excitation repeatability was produced, and drug imaging detection was performed in combination with a smartphone electrochemiluminescence microscope.
The visual detection of drug captopril is realized, providing a highly selective and efficient imaging method, suitable for the study of pharmacokinetics, dynamic processes of drug molecules and drug action mechanism, and provides new strategies for pharmacological research and drug screening. .
Smart Images

Figure CN119125266A_ABST
Abstract
Description
Technical Field
[0001] The invention relates to an electrochemiluminescent sensor, and in particular to a Zn-MOF@Ru / MIP electrochemiluminescent sensor, a preparation method and application thereof, and a method for visually detecting drug captopril by using the sensor. Background Art
[0002] Drug imaging technology is an emerging technology based on molecular imaging. Through molecular imaging and imaging systems, it can realize real-time and dynamic monitoring of drug distribution, metabolism and efficacy in the human body, providing a more accurate, timely and comprehensive diagnostic and therapeutic means for clinical treatment. Captopril (CTP) is the first approved angiotensin-converting enzyme inhibitor drug. It has a significant antihypertensive effect on various types of hypertension, but its excessive use can lead to renal damage and renal failure. Therefore, it is of great significance to establish a simple, fast, accurate and sensitive method for determining captopril to guide clinical drug use. At present, colorimetry, electrochemical method, fluorescence method and liquid chromatography-mass spectrometry are mainly used to determine captopril, but these methods are currently unable to perform drug imaging detection. Drug imaging technology can be used to analyze the distribution of drugs and their metabolites in the body in situ, visualize the interaction between drugs and target molecules, study the pharmacological activity of drugs, and perform drug screening. Therefore, it is very valuable to develop a simple, fast, cost-effective and portable method for rapid imaging detection of CTP.
[0003] Electrochemiluminescence (ECL) is a process that converts input electrical energy into light energy output through chemical reactions. Due to the change in energy form, this method has the advantages of near-zero background signal, high sensitivity, and high spatiotemporal resolution. In recent years, researchers have combined electrochemiluminescence with optical microscopy to construct an electrochemiluminescence microscope (ECLM). The high cost and difficulty of assembly of traditional ECLM devices have hindered the promotion of this technology to a certain extent. Currently, ECLM has been widely used in the study of mechanism pathways, bacteria, cell and organelle imaging, single particle tracing, single molecule imaging, protein corona formation dynamics, and single cell quantitative analysis. However, there is currently no ECLM-based quantitative drug imaging method.
[0004] The introduction of functional units with specific recognition capabilities can improve the selectivity of drug imaging quantitative analysis. Molecularly imprinted polymers (MIPs) are artificial receptors that can form cavities with specific recognition sites in the polymer after removing the template. They have the advantages of stable physicochemical properties, simple synthesis process, low cost, good selectivity, good versatility, and predictable structure. The inventor team of this application uses methacrylic acid as a monomer, and constructs an electrochemiluminescence sensor for detecting colchicine by combining Tg-CNNSs with molecular imprinting polymers (Wu Y, Qin D, Luo Z, Hu S, Xu L, Deng B. Construction of a smartphone-based electrochemiluminescence imaging device to guide the improvement of sensing performance via surface regulation [J]. Sensors and Actuators B: Chemical, 2023, 389: 133885.); At the same time, the inventor team of this application uses the electrochemiluminescence sensor and the self-developed smartphone-based ECLM (Smartphone-based ECLM, SECLM) to achieve visual detection of colchicine, but it has not been achieved. The inventor of this application analyzed that it may be because the ECL intensity of Tg-CNNSs is not enough.
[0005] Metal-organic framework (MOF) is a porous material with adjustable structure and size, excellent porosity and large specific surface area. It has been applied in the fields of sensors, catalysis and drug delivery. At present, the application of MOF in ECLM needs to be developed. However, there is no report on the use of CTP as a template, Zn-MOF@Ru combined with MIP to construct visual detection for CTP drug imaging. Summary of the invention
[0006] The technical problem to be solved by the present invention is to provide a Zn-MOF@Ru / MIP electrochemiluminescence sensor with excellent electrochemiluminescence performance and continuous excitation repeatability, a preparation method and application thereof, and a method for visually detecting the drug captopril using the sensor.
[0007] The first object of the present invention is to provide a method for preparing a Zn-MOF@Ru / MIP electrochemiluminescent sensor, specifically, a Zn-MOF@Ru aqueous solution is dripped on the surface of an electrode, dried, a film-forming agent solution is dripped on the surface of the Zn-MOF@Ru layer, and after the film is dried to form a film, a solution containing a molecular imprinting polymer with captopril as a template is dripped on the surface of the film, and dried to obtain the Zn-MOF@Ru / MIP electrochemiluminescent sensor; wherein Zn-MOF@Ru is a zinc-based metal organic framework-tri(2,2′-bipyridyl)ruthenium complex.
[0008] In this application, Zn-MOF@Ru / MIP represents a zinc-based metal organic framework-tris(2,2′-bipyridyl)ruthenium molecular imprinting complex. The Zn-MOF@Ru involved is specifically a composite material obtained by embedding tris(2,2′-bipyridyl)ruthenium (tris(2,2'-bipyridyl)ruthenium, Ru-bpy) into a zinc-based metal organic framework (Zn-MOF), which can be prepared by existing conventional methods, such as referring to existing literature (Zhao G, Wang Y, LiX, Yue Q, Dong X, Du B, Cao W, Wei Q. Dual-quenching electrochemiluminescence strategy based on three-dimensional metal–organic frameworks for ultrasensitive detection of amyloid-β[J]. Analytical Chemistry, 2019, 91: 1989–1996.). The molecularly imprinted polymer with captopril as a template is prepared by existing technology, such as referring to the existing literature (Zhang Y, Cui Y, Sun M, Wang T, Liu T, Dai X, Zou P, Zhao Y, Wang X, WangY, Zhou M, Su G, Wu C, Yin H, Rao H, Lu Z. Deep learning-assisted smartphone-based molecularly imprinted electrochemiluminescence detection sensing platform: Protable device and visual monitoring furosemide[J]. Biosensors and Bioelectronics, 2022, 209: 114262.).
[0009] In the above-mentioned preparation method of the Zn-MOF@Ru / MIP electrochemiluminescent sensor, the concentration of the Zn-MOF@Ru aqueous solution is usually limited to 1-3 mg / mL. In this method, the drying involved refers to natural drying at room temperature, and the drying film formation involved refers to natural drying film formation at room temperature.
[0010] In the preparation method of the above-mentioned Zn-MOF@Ru / MIP electrochemiluminescent sensor, the film-forming agent involved is chitosan or nafion solution. When the film-forming agent is chitosan, the film-forming agent solution is an aqueous solution of chitosan. Based on the poor solubility of chitosan in water, it is chosen to be dissolved under acidic conditions. At this time, the film-forming agent solution is preferably a chitosan aqueous solution with a concentration of 0.1 to 0.3 wt% (the pH of the solvent water is 3 to 5, adjusted with acetic acid or other conventional acids). When the film-forming agent is a nafion solution, the film-forming agent solution is preferably a nafion solution with a concentration of 0.05 to 0.1 wt%.
[0011] In the preparation method of the above-mentioned Zn-MOF@Ru / MIP electrochemiluminescent sensor, the solution containing the molecular imprinting polymer with captopril as the template is prepared by adding an appropriate amount of film-forming agent with water as the solvent and the molecular imprinting polymer with captopril as the template as the solute. The selection of the film-forming agent in the solution and its concentration in the solution are as described above. The amount of the solution containing the molecular imprinting polymer with captopril as the template applied to the surface of the membrane is specifically required by the amount of the molecular imprinting polymer with captopril as the template loaded on the electrode. The test results of the applicant show that when the diameter of the electrode used is 3mm, the amount of the molecular imprinting polymer with captopril as the template loaded on the electrode is preferably 12 to 15μg, more preferably 14μg. There is no special requirement for the concentration of the solution containing the molecular imprinting polymer with captopril as the template, preferably 1 to 3mg / mL.
[0012] In the preparation method of the above Zn-MOF@Ru / MIP electrochemiluminescent sensor, the electrode can be a glassy carbon electrode, a gold electrode, a platinum electrode, an indium tin oxide electrode or a fluorinated indium tin oxide electrode, preferably a glassy carbon electrode. The specification of the electrode can be selected according to needs, and an electrode with a diameter of 1 to 10 mm is usually used, preferably an electrode with a diameter of 3 to 10 mm.
[0013] The second object of the present invention is to provide a Zn-MOF@Ru / MIP electrochemiluminescent sensor prepared by the above method. The applicant's experiments show that the sensor exhibits excellent luminescence performance and repeatability.
[0014] The third object of the present invention is to provide the application of the above-mentioned Zn-MOF@Ru / MIP electrochemiluminescence sensor in the imaging detection of the drug captopril.
[0015] The fourth object of the present invention is to provide a method for visually detecting the drug captopril using the above-mentioned Zn-MOF@Ru / MIP electrochemiluminescence sensor, comprising the following steps:
[0016] 1) Using an electrochemical workstation as a voltage source, an upright microscope as a magnification tool, and a smart phone as an image capture tool, a reaction cell is set under the upright microscope, the reaction cell is filled with a detection solution, and a working electrode, a reference electrode, and a counter electrode electrically connected to the electrochemical workstation are set in the reaction cell to construct a three-electrode system; wherein the working electrode is the above-mentioned Zn-MOF@Ru / MIP electrochemiluminescence sensor, and the setting position of the working electrode is directly opposite to the center of the objective lens of the upright microscope, and the detection solution is composed of a PBS buffer solution with a pH of 7.2 to 8.0 and a co-reactant, and the concentration of the co-reactant in the detection solution is 1.15 to 1.3 mmol / L;
[0017] 2) The test sample is dripped on the surface of the working electrode, rinsed with water after incubation, and placed in a reaction tank for imaging detection after drying to obtain an optical image of captopril in the sample; when the concentration of captopril in the test sample is not within the linear range of detection, it is first diluted with a diluent, and the diluent is a PBS buffer with a pH of 4.5 to 5.2.
[0018] In step 1) of the above method, the three-electrode system constructed is similar to the imaging device disclosed in the previous research results of the applicant (Wu Y, Qin D, Luo Z, Hu S, Xu L, Deng B. Construction of a smartphone-based electrochemiluminescence imaging device to guide the improvement of sensing performance via surface regulation [J]. Sensors and Actuators B: Chemical, 2023, 389: 133885.), except that the working electrode is different, the others are the same. In the constructed three-electrode system, Ag / AgCl electrode is usually used as the reference electrode, and the platinum electrode is used as the counter electrode. The working electrode is below the upright microscope and directly opposite to the center of the upright microscope objective lens. When the specific detection is performed, according to the principle similar to the slide, the distance between the upright microscope objective lens and the working electrode is adjusted until a clear imaging position can be observed under the eyepiece. In this step, the co-reactant can be tripropylamine or dihydrazine hydrate, preferably tripropylamine. In a preferred embodiment, the detection solution is composed of a PBS buffer solution with a pH of 7.4 and a co-reactant, wherein the concentration of the co-reactant in the detection solution is 1.2 mmol / L. From the perspective of reducing background interference during shooting, it is preferred to place the upright microscope in a dark box.
[0019] In step 2) of the above method, when the incubation is carried out at room temperature, the applicant's test results show that under the above-mentioned limited conditions, as the incubation time increases, the quenching efficiency gradually increases and then remains basically unchanged, reaching the highest at 5 minutes, indicating that 5 minutes of incubation is sufficient for the drug to fully bind to the MIP. Therefore, the incubation time at room temperature is preferably greater than or equal to 5 minutes. In a preferred embodiment, the diluent is a PBS buffer with a pH of 5.
[0020] When the above method is used for detection, the excitation potential is set to 1.2 V, the exposure time is set to 10 s, and the sensitivity (ISO) is set to 6400.
[0021] Furthermore, the optical image (picture) obtained above can also be processed by software to obtain the gray value of the picture for quantitative imaging analysis (such as processing by Image J software (version: 1.53t, National Institutes of Health, USA) to obtain the mean gray value of the Red channel for quantitative imaging analysis). More specifically, the gray value of the obtained picture is used as the ordinate, and the captopril concentration corresponding to the gray value of the picture is used as the abscissa to make a standard working curve, and then the corresponding abscissa is found according to the gray value of the optical image obtained by testing the test sample, so as to determine the concentration of the drug captopril in the test sample.
[0022] Compared with the prior art, the Zn-MOF@Ru / MIP electrochemiluminescence sensor provided by the present invention exhibits excellent luminescence performance and repeatability (ΦECL=306%, RSD=4.0%). After being constructed with a molecular imprinting polymer with CTP as a template, it can be used for imaging detection of the drug captopril. Zn-MOF@Ru provides a sufficiently strong ECL signal for the imaging device, and the MIP with CTP as a template specifically binds to CTP, ensuring the high selectivity of the sensor. On the other hand, the successful visualization detection of CTP on the electrode surface provides a successful example for ECLM drug imaging and a new method for drug imaging detection, which is expected to be widely used in the fields of pharmacokinetics, drug molecular dynamics, drug action mechanism and drug toxicology, and provides a new strategy for promoting pharmacological research and drug screening. BRIEF DESCRIPTION OF THE DRAWINGS
[0023] Figure 1 Schematic diagram of the construction of the Zn-MOF@Ru / MIP sensor and the principle of drug imaging detection, as well as a schematic diagram of the constructed three-electrode system; (a) is a schematic diagram of the construction of the Zn-MOF@Ru / MIP sensor and the principle of drug imaging detection, and (b) is a schematic diagram of the constructed three-electrode system.
[0024] Figure 2 Various characterization spectra of the synthesized Zn-MOF@Ru material; including: (A) scanning electron microscope image, (A1-A4) element mapping image, (B) X-ray powder diffraction spectrum, (C) UV-visible absorption spectrum and ECL spectrum, (D) FTIR image, (E) Zeta potential of Zn-MOF and Zn-MOF@Ru, (F) nitrogen adsorption-analysis isotherm curve, (G) DFT pore size distribution diagram; detection conditions: Zn-MOF@Ru: 0.05mg / mL (UV-vis), 0.25mg / mL 8μL (ECL); CTP: 0.01mol / L (UV-vis).
[0025] Figure 3 Effects of different experimental conditions on the Zn-MOF@Ru / MIP sensor; including: (A) pH value of buffer solution, (B) concentration of co-reactant TPA, (C) amount of MIP, (D) drug incubation time, (E) pH value of drug incubation environment, (F) ECL intensity of Zn-MOF@Ru synthesized with different amounts of Ru(bpy)3Cl2·6H2O, (G) repeatability of Zn-MOF@Ru under constant potential continuous excitation; detection conditions: 0.1mol / L PBS buffer (pH=7.4, containing 1.2mmol / L TPA), excitation potential: 1.2V, exposure time: 10s, sensitivity (ISO): 6400, CTP: 1mmol / L, error bar = standard deviation, n=3.
[0026] Figure 4 Characterization diagram of the glassy carbon electrode (GCE) surface modified with different materials; (A) EIS spectrum, (B) CV curve; detection conditions: 0.1 mol / L PBS buffer (pH = 7.4, containing 1.2 mmol / LTPA), excitation potential: 1.2 V, exposure time: 10 s, sensitivity (ISO): 6400, CTP: 1 mmol / L.
[0027] Figure 5The method performance of the drug imaging detection platform at different CTP concentrations; including: (A) electrochemiluminescence imaging of GCE after incubation with different CTP concentrations, (B) linear relationship between CTP concentration and quenching efficiency of Zn-MOF@Ru / MIP sensor, (C) reproducibility between different electrodes, (D) selectivity of different interferents, (E) repeatability under constant potential excitation, (F) storage stability; detection conditions: 0.1mol / LPBS-1.2mmol / L TPA (pH=7.4), excitation potential of 1.2V, exposure time of 10s, sensitivity (ISO) of 6400, MIP volume of 7μL, incubation time of 5min, drug solvent: 0.1mol / L PBS (pH=5), (E) concentration of each substance in the figure is 100mmol / L, drug concentration: 10mmol / L (6μL), error bar = standard deviation, n=3. DETAILED DESCRIPTION
[0028] In order to better explain the technical solution of the present invention, the present invention is further described in detail below in conjunction with the embodiments, but the embodiments of the present invention are not limited thereto. If not specifically indicated, the technical features used in the embodiments can be replaced by other technical features known in the art that have equivalent or similar functions or effects without departing from the inventive concept.
[0029] Example 1
[0030] 1. Experimental part
[0031] 1.1 Instruments and reagents
[0032] Vario Micro Cube field emission environmental scanning electron microscope (Elementar, Germany); Cary-60 UV-visible spectrophotometer (Agilent Technologies, USA); Spectrum Two FT-IR Fourier transform infrared spectrometer (Perkin-Elmer, USA); Rigaku D / max 2500 / pc X-ray powder diffractometer (Rigaku, Japan); H1650-W high-speed centrifuge (Hunan Xiangyi Centrifuge Instrument Co., Ltd., China); electric constant temperature blast drying oven (Shanghai Qixin Technology Co., Ltd., China); CHI660 electrochemical workstation (Shanghai Chenhua Instrument Co., Ltd., China); MPI-B multi-parameter chemical analysis detection system (Xi'an Ruimai Analytical Instrument Co., Ltd., China).
[0033] All chemical reagents were used as received without further purification. Tripropylamine (TPA, AR) and chitosan (CTS, >400 mPa.s) were purchased from Shanghai Mailin Biochemical Technology Co., Ltd. (Shanghai, China). Ethylene glycol dimethacrylate (98 wt%), 2,2'-azobis(2-methylpropionitrile) (98 w / w%), L-cysteine (Cys, 99 w / w%), captopril (98 w / w%), Ru(bpy)3Cl2·6H2O (98 w / w%), and oxalic acid (99.5 w / w%) were purchased from Shanghai Aladdin Biochemical Technology Co., Ltd. (Shanghai, China). Methacrylic acid (99 wt%) was from Beijing Bailingwei Technology Co., Ltd. (Beijing, China). Sodium hydroxide (NaOH, 96 w / w%), acetic acid (AA, 99.5 wt%), glucose (Glu, AR), sodium chloride (NaCl, 99.5 w / w%), potassium chloride (KCl, 99.5 w / w%), urea (99 w / w%), calcium chloride (CaCl2, 90 w / w%), magnesium nitrate (MgNO3, 99 w / w%) and zinc nitrate hexahydrate (Zn(NO3)2·6H2O, 99 w / w%) were purchased from Xilong Chemical Co., Ltd. (Guangdong, China). Ultrapure water was used in the experiment.
[0034] 1.2 Synthesis of Zn-MOF@Ru
[0035] Zn-MOF@Ru was synthesized according to the existing literature (Zhao G, Wang Y, Li X, Yue Q, Dong X, Du B, Cao W, Wei Q. Dual-quenching electrochemiluminescence strategy based on three-dimensional metal–organic frameworks for ultrasensitive detection of amyloid-β[J]. Analytical Chemistry, 2019, 91: 1989–1996.). The specific synthesis process is as follows:
[0036] Weigh 60mg Ru(bpy)3Cl2·6H2O and 100mg Zn(NO3)2·6H2O, disperse in 45mL DMF / H2O (2:1, volume ratio), add 300μL oxalic acid (0.75mol / L, DMF dissolved) and 3mL hydrochloric acid (3mol / L), ultrasonicate for 5min to make it dispersed evenly, place in 75℃ oil bath to react for 24h. After cooling naturally, wash with DMF, ethanol and pure water three times respectively, and finally dry in a vacuum drying oven at 50℃ to obtain Zn-MOF@Ru, which is stored at 4℃ for later use.
[0037] 1.3 Preparation of molecularly imprinted polymer (MIP) with captopril as template
[0038] Refer to the existing literature (Zhang Y, Cui Y, Sun M, Wang T, Liu T, Dai X, Zou P, Zhao Y, Wang andBioelectronics,2022,209:114262.) Prepare MIP, the specific method is as follows:
[0039] 0.2090 g of captopril (32 mmol / L) was used as a template, 81.5 μL of methacrylic acid (32 mmol / L) was used as a monomer, and methanol-acetonitrile (v / v=1:2, volume ratio, 30 mL) was used as a solvent. After mixing, the mixture was ultrasonicated for 20 min and refrigerated at 4°C for 24 h to obtain a prepolymerized MIP through hydrogen bonding. 150 μL of ethylene glycol dimethacrylate and 20 mg of azobisisobutyronitrile were added to 8 mL of prepolymerized MIP, ultrasonicated for 10 min, and nitrogen was introduced for 10 min to remove dissolved oxygen after mixing evenly. The mixture was reacted in a 65°C water bath for 2 h under nitrogen protection to obtain a solid polymer (i.e., a molecularly imprinted polymer containing captopril drug). 5 mL of NaOH (0.25 mol / L) was added and stirred for 20 min, and then the supernatant was removed by centrifugation. The mixture was repeated 3 times to elute the drug. Finally, the mixture was washed three times with ultrapure water and ethanol respectively, and dried in a 60°C vacuum drying oven to obtain a white solid MIP, which was stored in a 4°C refrigerator for later use.
[0040] 1.4 Preparation of Zn-MOF@Ru / MIP electrochemiluminescence sensor
[0041] First, the glassy carbon electrode (diameter 3mm, GCE) was polished to a mirror surface with 0.3 and 0.05μm Al2O3 powder on a polishing cloth, ultrasonicated with ethanol / ultrapure water for 1min, and finally dried with nitrogen for use. 8μL 1mg / mL Zn-MOF@Ru aqueous solution was drop-coated on the surface of the glassy carbon electrode and dried naturally at room temperature. Then 4μL 0.2wt% chitosan-3wt% acetic acid solution (i.e., an aqueous solution containing 0.2wt% chitosan and 3wt% acetic acid) was covered on the surface of the Zn-MOF@Ru layer. After it dried to form a film, 7μL MIP (2mg / mL)-0.2wt% chitosan-3wt% acetic acid solution (i.e., an aqueous solution containing 2mg / mL of the MIP prepared in Section 1.3 above, 0.2wt% chitosan and 3wt% acetic acid) was covered on it and dried naturally to obtain a Zn-MOF@Ru / MIP electrochemiluminescent sensor. Schematic diagram of the construction of Zn-MOF@Ru / MIP electrochemiluminescence sensor and drug imaging detection principle Figure 1 (a) shown.
[0042] 1.5 Electrochemiluminescence imaging
[0043] 6 μL of a certain concentration of CTP solution (solvent: 0.1 mol / L PBS buffer at pH = 5) was drop-coated on the surface of the Zn-MOF@Ru / MIP electrochemiluminescent sensor prepared in Section 1.4 above, incubated at room temperature for 5 min, and rinsed with ultrapure water.
[0044] The three-electrode system of the present application (electrochemiluminescence microscopy based on a smartphone (Smartphone-based Electrochemiluminescence microscopy, hereinafter also referred to as SECLM device) is constructed with reference to the imaging device disclosed in the previous research results of the present applicant (Wu Y, Qin D, Luo Z, Hu S, Xu L, Deng B. Construction of a smartphone-based electrochemiluminescence imaging device to guide the improvement of sensing performance via surface regulation [J]. Sensors and Actuators B: Chemical, 2023, 389: 133885.), as shown in detail. Figure 1 (b) is shown. Figure 1In (b), an electrochemical workstation is used as a voltage source, an upright microscope is used as a magnification tool, and a smart phone is used as an image capture tool. The smart phone is located above the upright microscope, and its camera is facing the eyepiece of the upright microscope to capture the image. A reaction cell is arranged below the upright microscope, and the reaction cell is filled with a detection solution. The reaction cell is provided with a working electrode, a reference electrode, and a counter electrode electrically connected to the electrochemical workstation. The working electrode is the Zn-MOF@Ru / MIP electrochemiluminescence sensor prepared above, and the working electrode is arranged below the upright microscope and facing the center of the objective lens of the upright microscope. An Ag / AgCl electrode is used as the reference electrode, and a platinum electrode is used as the counter electrode.
[0045] The electrochemiluminescence imaging parameters were set as follows: 1.2 V excitation potential, 10 s exposure time, 6400 sensitivity (ISO). Optical images were obtained using a SECLM device. The images were processed using Image J software (version: 1.53t, National Institutes of Health, USA) to obtain the mean gray value of the Red channel for quantitative imaging analysis.
[0046] 1.6 Determination of electrochemical luminescence efficiency
[0047] Relative ECL efficiency of Zn-MOF@Ru (Φ ECL ) is based on Ru(bpy)3 2+ / TPA is used as the benchmark and is measured by comparing the ratio of generated photons to consumed electrons. The specific equation is as follows:
[0048]
[0049] Where "ECL" and "Current" are ECL intensity (unit: au) and current value (unit: A), "x" represents Zn-MOF@Ru / TPA, and "st" represents Ru(bpy)3 2+ / TPA.
[0050] 2. Results and Discussion
[0051] 2.1 Material characterization
[0052] To verify the successful synthesis of Zn-MOF@Ru, we used scanning electron microscopy (SEM), X-ray powder diffractometer (XRD), ultraviolet visible absorption spectrophotometer (UV-vis), fluorescence spectrophotometer (FL), Fourier transform infrared spectrometer (FTIR), Zeta potential instrument and physical adsorption instrument to characterize it. The results are shown in Figure 2As shown in the SEM image, Zn-MOF@Ru has a typical octahedral structure ( Figure 2 A), from the element mapping, it can be found that Zn-MOF@Ru is mainly composed of Zn, C, O, Ru and other elements, indicating that Ru-bpy is successfully embedded in Zn-MOF ( Figure 2 A1-A4); XRD characterizes the crystal structure of the material, and the results show that Zn-MOF@Ru has good crystal structure and crystallinity ( Figure 2 B) The above results show that embedding Ru-bpy will not destroy the integrity of the Zn-MOF framework. At the same time, the ordered crystal structure is conducive to electron transfer during the electrochemical reaction and increases the ECL efficiency.
[34] The UV-vis spectrum of Zn-MOF@Ru shows absorption peaks at 286nm and 452nm respectively ( Figure 2 C). From the ECL spectrum, it can be seen that the optimal emission wavelength of Zn-MOF@Ru is 650nm ( Figure 2 C). The characteristics of the UV-vis absorption peak and ECL emission peak of Zn-MOF@Ru are both from Ru-bpy, indicating the successful synthesis of Zn-MOF@Ru. From the FTIR spectrum, we can see that ( Figure 2 D), 1316cm -1 and 1599cm -1 The absorption peaks at 3082cm correspond to the characteristic absorption peaks of CO and C=O stretching vibration, respectively. -1 The absorption peak at is the stretching vibration peak of OH, which indicates that there are a large number of carboxyl groups on the surface of Zn-MOF@Ru. The carboxyl groups mainly come from the ligand oxalic acid. The presence of carboxyl groups not only provides electrostatic force for the enrichment of Ru-bpy, but also guarantees its hydrophilicity. Through the characterization of the Zeta potential of Zn-MOF and Zn-MOF@Ru, it can be found that the potential of Zn-MOF is -10.02mV, and the surface is negatively charged, while Ru(bpy)3 2+ It is a positive divalent ion with a positive charge, so the two can be combined by electrostatic force. The Zeta potential of Zn-MOF@Ru is -6.12mV ( Figure 2 E), indicating that Ru(bpy)3 2+ Successfully combined with Zn-MOF. To further verify that Ru-bpy is embedded in the pores of Zn-MOF, we characterized the nitrogen adsorption-analysis isotherms and Density functional theory (DFT) pore size distribution of Zn-MOF and Zn-MOF@Ru at 77K. The specific surface areas of Zn-MOF and Zn-MOF@Ru were 1.1508 m 2 / g and 1.0329m2 / g, and the total pore volume is 0.003746cm 3 / g and 0.001805cm 3 / g, and the average pore diameters are 6.808nm and 4.645nm respectively ( Figure 2 F). At the same time, the pore size distribution of Zn-MOF and Zn-MOF@Ru was obtained based on the DFT model. Figure 2 G. By comparing the specific surface area, total pore volume of single-point adsorption and average pore size of desorption, it can be found that compared with Zn-MOF, the specific surface area, pore volume and pore size of Zn-MOF@Ru are significantly smaller, indicating that Ru-bpy is embedded in the pores of Zn-MOF.
[0053] 2.2 Optimization of detection conditions
[0054] To achieve the best sensor performance, we optimized the parameters such as the pH value of the buffer solution, the concentration of the co-reactant TPA, the amount of MIP, the drug incubation time and the pH value of the drug incubation environment. Figure 3 shown.
[0055] The pH value of the detection solution and the concentration of the co-reactant are closely related to the luminescence performance of the luminophore. When the pH value of the detection solution increases from 5 to 9, the ECL intensity first increases and then decreases, reaching the highest value at 7.4 ( Figure 3 A); When the co-reactant concentration increases from 0.8mmol / L to 1.6mmol / L, the ECL intensity first increases, reaches the highest at 1.2mmol / L, and then tends to be stable ( Figure 3 B). Therefore, PBS buffer (containing 1.2 mmol / L TPA) with a pH of 7.4 was selected as the detection solution.
[0056] MIP is a polymer with a porous structure. The amount of MIP not only determines the number of drug binding sites, but also affects the luminescence performance of the luminophore. Therefore, choosing the appropriate amount of MIP is of great significance to improving sensor performance. When the amount of MIP increases from 4 μL to 8 μL, the quenching efficiency increases first and then decreases ( Figure 3 C), indicating that too much MIP hinders the contact between the co-reactant and the luminophore and increases the resistance, thereby affecting the sensitivity of the sensor. Therefore, 7 μL of MIP was selected to construct the Zn-MOF@Ru / MIP sensor.
[0057] The pH value of the drug incubation environment and the reaction time both affect the binding efficiency. As the reaction time increases, the quenching efficiency gradually increases and then remains basically unchanged, reaching the highest at 5 minutes, indicating that 5 minutes of incubation is sufficient for the drug to fully bind to MIP ( Figure 3D); When the pH value of the drug incubation environment is 5, the quenching efficiency reaches the best, indicating that at this pH, the ionization state of CTP has the strongest binding ability with MIP ( Figure 3 E), therefore, PBS buffer with pH = 5 was selected to dissolve the drug and incubated for 5 min to ensure optimal sensor performance.
[0058] 2.3 Investigation of Ru-bpy dosage and luminescence performance of Zn-MOF@Ru
[0059] Developing a luminophore with excellent luminescence performance and continuous excitation repeatability is a prerequisite for realizing a drug imaging detection platform. In order to obtain a luminophore with the best performance, we explored the optimal ratio of Zn-MOF and Ru-bpy. Except for Ru-bpy, the amounts of other raw materials remained unchanged. As the dose of Ru-bpy increased, the ECL intensity gradually increased and reached a plateau value at 60 mg. Further addition of Ru-bpy had no effect on the ECL intensity, indicating that the Ru-bpy in Zn-MOF reached equilibrium ( Figure 3 F). Therefore, 60 mg of Ru-bpy was used to synthesize the Zn-MOF@Ru luminescent body. Figure 3 G shows that the synthesized Zn-MOF@Ru exhibits good reproducibility (RSD = 4.0%) under constant potential continuous excitation. ECL Assuming it is 100%, the Φ of Zn-MOF@Ru is calculated by the formula ECL It is 306% (see 1.6 for the determination method), indicating that the luminescence efficiency of Zn-MOF@Ru is twice as high as that of Ru-bpy. We believe that the excellent luminescence performance of Zn-MOF@Ru is due to the good conductivity, high specific surface area and porosity of Zn-MOF, and the embedding of a large amount of Ru-bpy, thus producing an excellent and stable ECL signal.
[0060] 2.4 Sensor Construction
[0061] In order to confirm the successful construction of the sensor, it was characterized by electrochemical impedance spectroscopy and CV curves. Figure 4 As shown in A, the impedance of Zn-MOF is higher than that of Zn-MOF@Ru, while the impedance of Zn-MOF@Ru is close to that of the bare electrode, indicating that Ru-bpy improves the conductivity of Zn-MOF (curves a, b, c), which helps to improve the electrochemical activity of the luminophore; when modified with MIP, the impedance increases significantly (curve e), indicating that the conductivity of MIP is poor; after drug incubation, the impedance increases further (curve f), indicating that the drug successfully combines with MIP and increases the resistance. Figure 4The same conclusion can be drawn in B. After adding MIP and incubating drugs, the peak current of the CV curve decreased significantly. The above results prove that Zn-MOF@Ru / MIP and CTP are successfully constructed.
[0062] 2.5 Analytical Performance
[0063] To explore the performance of the drug imaging detection platform, we measured different concentrations of CTP under optimized conditions. Figure 5 As shown in Figure 2, with the increase of CTP concentration, the brightness of the Zn-MOF@Ru / MIP sensor gradually decreased ( Figure 5 A), the results are intuitive and visual, indicating that this method is suitable for drug imaging. The quenching efficiency is calculated using the grayscale values before and after the addition of the drug. The results are shown in Figure 5 As shown in B, the CTP concentration and quenching efficiency are in the range of 1-1×10 5 There is a good linear relationship between them, and the linear equation is (G0-G / G0)=0.1179lgC+0.1413, R 2 =0.9983, and the detection limit was 0.29 μmol / L (n=11). This indicates that the spatially resolved drug imaging quantitative method has been verified. Compared with the reported methods (Table 1), this method has the advantages of simple device, high efficiency, wide linear range, and intuitive visualization of results.
[0064] Table 1 Comparison of the performance of the method of the present invention and other analytical methods
[0065]
[0066] [1]: Yuan MY, Xiao SJ, Wu YN, Qiu AT, Guo J, Zhong ZQ, Zhang L.Visual detection of captopril based on the light activated oxidase-mimic activity ofcovalent organic framework[J].Microchemical Journal, 2022,175:107080.
[0067] [2]: Gimenes DT, Marra MC, De Freitas JM, Abarza RA,Richter EM.Simultaneous determination of captopril and hydrochlorothiazide on boron-doped diamond electrode by batch injection analysis with multiple pulseamperometric detection[J].Sensors and Actuators B:Chemical,2015,212:411–418.
[0068] [3]: Jiang X, Qin D, Mo G, Feng J, Zheng X, Deng B. Facile preparation of boron and nitrogen codoped green emission carbon quantum dots for detection of permanganate and captopril[J]. Analytical Chemistry, 2019,91:11455–11460.
[0069] [4]: Vancea S, Imre S, Donáth-Nagy G, Béla T, Nyulas M, Muntean T, Borka-Balás R. Determination of free captopril in human plasma by liquid chromatography with mass spectrometry detection[J]. Talanta, 2009,79:436–441.
[0070] 2.6 Reliability of Zn-MOF@Ru / MIP sensor
[0071] To verify the reliability of the Zn-MOF@Ru / MIP sensor, we investigated the performance of the Zn-MOF@Ru / MIP sensor in terms of reproducibility, selectivity, repeatability, and stability. Figure 5 C shows that the performance of Zn-MOF@Ru / MIP on different electrodes is basically the same, indicating that the sensor has good reproducibility between different electrodes (RSD = 1.4%). To verify the selectivity of the sensor, we investigated the effects of common ions and biomolecules in plasma on it. The results show that common substances in plasma have little effect on the performance of the sensor ( Figure 5D) From Figure 5 As can be seen in E, thanks to the repeatability of the luminophore, under constant potential continuous excitation, Zn-MOF@Ru / MIP also showed excellent repeatability (RSD = 0.9%), and the repeatability was better than that of the single luminophore. This may be due to the modification of chitosan and MIP. The luminophore is confined to the electrode surface, which inhibits the diffusion of the luminophore into the solution, thereby enhancing its repeatability. Figure 5 It can be seen from Figure F that after the sensor was stored at 4°C for 4 weeks, the luminescence performance did not show significant attenuation (RSD = 1.6%), indicating that the sensor has good stability. The above results show that the Zn-MOF@Ru / MIP sensor has good reliability and has prospects for practical application.
[0072] Experimental Example 1: Determination of CTP content in mouse plasma
[0073] In order to finally confirm whether the drug imaging detection platform based on Zn-MOF@Ru / MIP sensor has the ability to be applied in practice, we used mouse plasma as a sample to detect the CTP content in plasma. The plasma sample was processed as follows:
[0074] BALB / c female mice (6–8 weeks old) were purchased from Hunan Slake Jingda Experimental Animal Company (Changsha, China). Animal handling methods were performed in accordance with the approval of the Animal Ethics Committee of Guangxi Normal University (GXNU-202303-051).
[0075] After fasting for one day, mice were allowed to drink water freely and were given 10 mg CTP / kg body weight by gavage. The control group was given the same dose of deionized water. Two hours after administration, the blood of the mice was drawn into a centrifuge tube treated with sodium heparin and centrifuged at 3500 rpm for 15 minutes to obtain the supernatant, which was plasma.
[0076] In order to make the CTP concentration in the blood sample fall within the linear range and ensure the pH value of the blood sample, we diluted the plasma sample 10 times with PBS buffer at pH = 5 and used the spike recovery method to determine the accuracy and precision of the method. The results are shown in Table 2.
[0077] Table 2 Determination results and spike recovery of CTP in mouse plasma based on drug imaging platform (n=5)
[0078]
[0079] As shown in Table 2, the spiked recovery of the method constructed by the present invention is between 97.2% and 102.2%, and the relative standard deviation (RSD, n = 5) is less than 3%. The above results show that the method has high accuracy and good precision, and has practical application value and potential.
[0080] In summary, we prepared a composite material of Ru-bpy embedded in Zn-MOF (Zn-MOF@Ru). Zn-MOF@Ru showed excellent luminescence performance and repeatability (ΦECL=306%, RSD=4.0%). On this basis, CTP imaging detection based on SECLM was developed. The drug imaging method constructed by the present invention can obtain a picture in just ten seconds. This method is expected to be widely used in pharmacokinetic research, drug molecular dynamics, drug action mechanism research and drug toxicology research, and provide a new strategy to promote pharmacological research and drug screening.
Claims
1. A method for preparing a Zn-MOF@Ru / MIP electrochemiluminescence sensor, characterized in that: A Zn-MOF@Ru aqueous solution is dripped on the surface of the electrode and dried, a film-forming agent solution is dripped on the surface of the Zn-MOF@Ru layer, and after it dries to form a film, a solution containing a molecular imprinting polymer with captopril as a template is dripped on the surface of the film and dried to obtain the Zn-MOF@Ru / MIP electrochemiluminescent sensor; wherein Zn-MOF@Ru is a zinc-based metal organic framework-tri(2,2′-bipyridyl)ruthenium complex.
2. The preparation method according to claim 1, characterized in that: When the diameter of the electrode used is 3 mm, the amount of the molecular imprinting polymer with captopril as a template loaded on the electrode is 12-15 μg.
3. The preparation method according to claim 1, characterized in that: The solution containing the molecular imprinting polymer with captopril as a template is prepared by taking water as a solvent, taking the molecular imprinting polymer with captopril as a template as a solute, and adding a proper amount of a film-forming agent.
4. The preparation method according to any one of claims 1 to 3, characterized in that: The film-forming agent is chitosan or nafion solution.
5. The preparation method according to any one of claims 1 to 3, characterized in that: The electrode is a glassy carbon electrode, a gold electrode, a platinum electrode, an indium tin oxide electrode or a fluorinated indium tin oxide electrode.
6. The Zn-MOF@Ru / MIP electrochemiluminescence sensor prepared according to the method according to any one of claims 1 to 5.
7. Application of the Zn-MOF@Ru / MIP electrochemiluminescence sensor according to claim 6 in imaging detection of the drug captopril.
8. A method for visually detecting the drug captopril using the Zn-MOF@Ru / MIP electrochemiluminescence sensor according to claim 6, comprising the following steps: 1) Using an electrochemical workstation as a voltage source, an upright microscope as a magnification tool, and a smart phone as an image capture tool, a reaction cell is set under the upright microscope, the reaction cell is filled with a detection solution, and a working electrode, a reference electrode, and a counter electrode electrically connected to the electrochemical workstation are set in the reaction cell to construct a three-electrode system; wherein the working electrode is the Zn-MOF@Ru / MIP electrochemiluminescence sensor according to claim 6, the setting position of the working electrode is directly opposite to the center of the objective lens of the upright microscope, and the detection solution is composed of a PBS buffer solution with a pH of 7.2 to 8.0 and a co-reactant, and the concentration of the co-reactant in the detection solution is 1.15 to 1.3 mmol / L; 2) The test sample is dripped on the surface of the working electrode, rinsed with water after incubation, and placed in a reaction tank for imaging detection after drying to obtain an optical image of captopril in the sample; when the concentration of captopril in the test sample is not within the linear range of detection, it is first diluted with a diluent, and the diluent is a PBS buffer with a pH of 4.5 to 5.
2.
9. The method according to claim 8, characterized in that: In step 1), the co-reactant is tripropylamine or dihydrazine hydrate.
10. The method according to claim 8, characterized in that: In step 2), when the incubation is carried out at room temperature, the incubation time is ≥ 5 min.
